Postoperative 'STEMI' in Intracerebral Hemorrhage due to Arteriovenous Malformation: A Case Report and Review of Literature. (22nd April 2019) - Bhanot, Ravinder Datt; Kaur, Jasleen; Sriwastawa, Shitiz; Bell, Kendall; Suchdev, Kushak
Abstract : Electrocardiogram (ECG) changes suggestive of cardiac ischemia are frequently demonstrated in patients with ischemic stroke and subarachnoid hemorrhage. However, little is known of such changes particularly acute ST segment myocardial infarction (STEMI) in patients with intracerebral hemorrhage (ICH), especially after neurosurgery. We present a patient with intraparenchymal hemorrhage due to cerebral arteriovenous malformation (AVM) who exhibited acute STEMI after neurosurgery. Serial cardiac biomarkers and echocardiograms were performed which did not reveal any evidence of acute myocardial infarction. The patient was managed conservatively from cardiac stand point with no employment of anticoagulants, antiplatelet therapy, fibrinolytic agents, or angioplasty and recovered well with minimal neurological deficit. This case highlights that diffuse cardiac ischemic signs on the ECG can occur in the setting of an ICH after neurosurgery, potentially posing a difficult diagnostic and management conundrum.